Problem Pembelajaran Online di Masa Pandemi terhadap Psikologi Anak Usia 10-12 Tahun - Rismag Dalena Florentina Monica Br Manurung; Talizaro Tafonao (Institut Agama Kristen negeri Kupang, 2021)
The purpose of this article was to increase a parent's understanding of the importance of child assistance during online study during the pandemic. In the study the authors found that almost all children complained with online learning activities at home. Furthermore, a parent's minimum of supervision is during online study. The result of this problem is that children suffer from a psychological breakdown. This is seen in the unencouraging children's attitudes at online learning as described in this article. The methods used are qualitative research methods that discuss how much online learning problems affect child psychology. The analysis process is to use reliable sources of both journals, books, interviews and other reference materials to support the writer's analysis. The results found by the author are a significant indication of what parental involvement might be when applying the learning methods found in Deuteronomy. Thus, all the excuses people have complained about over the years are that teaching a child in the harvest has become a burden. These reasons are not fully accepted because the responsibility of teaching, educating and guiding becomes the full responsibility of the parents as it is Explanations in the study.